Promoting Paternal Participation in Maternal and Child Health Services. Issue 2 (14th March 2016) - Perry, Armon R.; Rollins, Aaron; Sabree, Ramzi; Grooms, Wes
ABSTRACT: Social service organizations face significant challenges involving fathers. This study presents the findings of a project between a maternal and child health program and a school of social work aimed at enhancing the organization's capacity for engaging fathers in services. Results revealed that staff expressed a willingness to engage fathers but felt unprepared to do so. In detailing their experiences with the organization, fathers discussed the ways in which they had been engaged and their recommendations for improving those efforts. We conclude by advocating for the adoption of a bottom-up philosophy with regard to fatherhood program development and service delivery.